VD_FINDINFO Décision / 2014 / 21 vom 16. Dezember 2013 - VD Tribunal cantonal (2013)
CHIEN, SURVEILLANCEEN GÉNÉRAL, LÉSION CORPORELLE PAR NÉGLIGENCE, NÉGLIGENCE | 12 al. 3 CP, 125 CP, 319 al. 1 CPP (CH)